Complementary and Alternative Medicine: Comparison of Current Knowledge, Attitudes and Interest among German Medical Students and Doctors. (18th June 2011) - Münstedt, Karsten; Harren, Hildegard; von Georgi, Richard; Hackethal, Andreas
Abstract : Although it has been agreed that complementary and alternative medicine (CAM) should be included in the German medical curriculum, there is no consensus on which methods and how it should be taught. This study aimed to assess needs for CAM education by evaluating current knowledge, attitudes and interests of medical students, general physicians and gynecologists. Two instruments based on established and validated questionnaires were developed. One was given to seventh semester medical students and the other to office-based doctors. Data were analyzed by bivariate correlation and cross-tabulation. Altogether 550 questionnaires were distributed—280 to doctors and 270 to medical students. Completed questionnaires were returned by 80.4% of students and 78.2% of doctors. Although 73.8% (160/219) of doctors and 40% (87/217) of students had already informed themselves about CAM, neither group felt that they knew much about CAM. Doctors believed that CAM was most useful in general medicine, supportive oncology, pediatrics, dermatology and gynecology, while students believed that dermatology, general medicine, psychiatry and rheumatology offered opportunities; both recommended that CAM should be taught in these areas. Both groups believed that CAM should be included in medical education; however, they believed that CAM needed more investigation and should be taught "critically". German doctors and students would like to be better informed about CAM. An approach which teaches fundamental competences to students, chooses specific content based on evidence, demographics and medical conditions and provides students with the skills they need for future learning should be adopted.